2019
DOI: 10.1021/acs.jafc.9b02925
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Milk Exosome MiRNAs Attenuate LPS-Induced Apoptosis through Inhibiting TLR4/NF-κB and p53 Pathways in Intestinal Epithelial Cells

Abstract: Lipopolysaccharide (LPS) is a bacterial endotoxin that induces intestine inflammation. Milk exosomes improve the intestine and immune system development of newborns. This study aims to establish the protective mechanisms of porcine milk exosomes on the attenuation of LPS-induced intestinal inflammation and apoptosis. In vivo, exosomes prevented LPSinduced intestine damage and inhibited (p < 0.05) LPS-induced inflammation. In vitro, exosomes inhibited (p < 0.05) LPSinduced intestinal epithelial cells apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 47 publications
1
120
1
Order By: Relevance
“…It has been proposed that exosomal miRNAs such as let-7, miR-21, and miR-29a, identified in oEVs, can act as an unconventional mode to activate TLR7 in mice and cause neurodegeneration and tumor growth and metastasis [59,60]. In the same line, milk exosomal miRNAs have been shown to decrease LPS-induced TLR4/NF-κB signaling pathway activation, reducing LPS-induced inflammation through the NF-κB pathway and inhibiting LPS-induced apoptosis via the p53 pathway [61]. Altogether, these data suggest that miRNAs present in oEVs could regulate components of TLR pathways in the embryo, modulating the maternal immune system at the maternal-fetal interface.…”
Section: Regulation Of the Embryonic Transcriptome By Oev-derived Mirmentioning
confidence: 98%
“…It has been proposed that exosomal miRNAs such as let-7, miR-21, and miR-29a, identified in oEVs, can act as an unconventional mode to activate TLR7 in mice and cause neurodegeneration and tumor growth and metastasis [59,60]. In the same line, milk exosomal miRNAs have been shown to decrease LPS-induced TLR4/NF-κB signaling pathway activation, reducing LPS-induced inflammation through the NF-κB pathway and inhibiting LPS-induced apoptosis via the p53 pathway [61]. Altogether, these data suggest that miRNAs present in oEVs could regulate components of TLR pathways in the embryo, modulating the maternal immune system at the maternal-fetal interface.…”
Section: Regulation Of the Embryonic Transcriptome By Oev-derived Mirmentioning
confidence: 98%
“…And numerous studies further showed that mEVs and their cargos played a critical role on attenuating LPS‐induced apoptosis, preventing the development of experimental necrotizing enterocolitis and promoting microbial growth. [ 15–17 ] In addition, mEVs could resist the harsh environment (low pH, high temperature, enzymatic treatment) of the gastrointestinal tract and reach the intestinal lumen. [ 18–20 ] Thus, mEVs might involve in several immunomodulatory mechanisms, intestinal tract development, and reshaping of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Whether nonabsorbed exosomes also act from the luminal side is not elucidated. Recent evidence indicates that milk exosomes play a critical role for intestinal maturation and function in humans and rodent models [22][23][24][25][26][27][28]. It has been demonstrated in murine models that human, bovine, and porcine milk exosomes support intestinal cell growth [22][23][24], attenuate LPS-induced apoptosis [25], prevent intestinal endothelial cell damage [26,27], enhance goblet cell numbers and mucin production [28], modify bacterial growth, and promote intestinal microbiota [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that milk exosomes play a critical role for intestinal maturation and function in humans and rodent models [22][23][24][25][26][27][28]. It has been demonstrated in murine models that human, bovine, and porcine milk exosomes support intestinal cell growth [22][23][24], attenuate LPS-induced apoptosis [25], prevent intestinal endothelial cell damage [26,27], enhance goblet cell numbers and mucin production [28], modify bacterial growth, and promote intestinal microbiota [29,30]. Accumulating evidence indicates that milk exosomes exert barrier-protective and anti-inflammatory effects in rodent models of necrotizing enterocolitis (NEC) and NEC in human infants [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%